New Species of Macroalgae from Tamengo Formation, Ediacaran, Brazil - Diniz, Cleber Q. C.; Leme, Juliana de Moraes; Boggiani, Paulo C. (Frontiers in Earth Science, 2021)
The Tamengo Formation (Corumbá Group) is an important ediacaran stratigraphic unit in South America due to metazoan fossils, preservation of primary geochemistry data of carbonate rocks and excellent geochronological delimitation (between 555 – 541 Ma), obtained by U-Pb datation on volcanic zircons. The present work shows three new species of macroalgae found as carbonaceous compressions and studied them for their morphology and taxonomy. All new taxa are characterized as centric macroalgae. Tamengophyton espinosa sp. nov. formed striated thalli, dichotomous branches, trichomes with perpendicular growth from the thallus and a connecting membrane. Ladariella hidria sp. nov. is formed by a set of striated and branched thallus in a cylindrical form with almond shaped structures in the tip. Ladariophyton veinosa sp. nov. is characterized by a thallus with main growth and a thick longitudinal structure in the center. These news occurrences of macroalgaes are the largest life assemblages in the Neoproterozoic of South America, which contributes to documentation of the evolutionary history of macroalgae and the paleoecological of the Late Ediacaran.